Immunological Factors Associated with Health Status of Heart Transplant Recipients Long-Term after Transplantation. (July 2018) - Gallego, Antonio; Sarmiento, Elizabeth; Sousa, Iago; Fernandez-Yañez, Juan; Palomo, Jesus; Navarro, Joaquin; Gil, Juana; Carbone, Javier
Abstract : Measures of the effects of health care on patients' lives is important to better evaluate transplantation outcomes. A relatively short, 36-item, questionnaire (SF-36) designed to measure health status is used as an outcome measure of health related quality of life (QoL) in distinct medical settings. We aimed to identify potential immunological abnormalities as factors associated with poorer QoL scores at distinct scales of the SF36 in heart transplant recipients long time after transplantation. The SF-36 was sent by mail to adult heart recipients (n = 160) as a pilot study of health related QoL applied to heart transplantation in our center. Immunological abnormalities that were evaluated as potential factors were IgG < 600 mg/dL, C4 < 20 mg/dL, C3 < 80 mg/dL, CD3 < 1000 cells/uL, CD4 < 500 cells/uL and CD8 < 400 cells/uL. All immunological parameters were evaluated more than one year after heart transplantation and before the SF-36 forms were mailed. Range of time after transplantation of participants was 4-21 years after transplantation. Response rate was 62.5% (100 patients). Male and female heart transplant recipients had lower scores for general health perceptions (50.4 +/- 22.1 versus 60.3 +/- 23.2 and 47.0 +/- 18.1 versus 53.7 +/- 22.5, respectively) compared with Spanish population reference values. Older recipients (p=0.04), post transplant diabetes (p=0.049), digestive complications (p=0.020) and post transplant infections (p=0.025) were factors associated with lower physical functioning scores (<60). Older recipients (p=0.04), digestive complications (p=0.031) and lower CD8 counts (p=0.007) were associated with lower physical role scores (<25). These preliminary data suggest that the SF-36 is sensitive to the long-term effects of heart transplantation. Lower CD8 counts were significantly associated with poorer physical role scores. Lower CD8 cell counts have been described as a risk factor of poorer outcomes in distinct chronic diseases. Taking into account that immunosuppressive drugs are continuously used by these patients at the doses necessary to suppress allograft rejection risk, additional studies of the potential role of immunological abnormalities as surrogates of health related QoL outcome measure for heart transplantation are warranted. Mutua Madrileña Grant to JC. Fondo de Investigación Sanitaria. Project FIS 1501472. With participation of FEDER funds. A way of making Europe.